S62. COGNITIVE DEFICITS IN TREATMENT RESISTANT SCHIZOPHRENIA. (18th May 2020) - Millgate, Edward; Kravariti, Eugenia; MacCabe, James; Hide, Olga
Abstract: Background: Schizophrenia (Sz) and other psychoses are complex mental disorders, characterised by sensory, cognitive and emotional symptoms, but mainly distinguished by positive and negative symptoms. Cognitive impairment is a core feature of schizophrenia, with research into cognitive deficits indicating that cognitive impairment precedes clinical disease onset and is still evident after positive symptoms are no longer present. The current mainstream treatment for Sz are first and second-generation antipsychotics, such as chlorpromazine and aripiprazole respectively. However, about a third of patients treated with antipsychotic drugs have no change in their symptoms despite adequate trials of several antipsychotic drugs. Treatment-resistant schizophrenia (TRS) refers to individuals with a F20-F29 diagnosis who have had at least two courses of antipsychotic treatment with little to no symptomatic relief. Emerging evidence into the factors associated with antipsychotic treatment response has investigated genetic, demographic and clinical factors and their relation to treatment response, with emerging evidence from cognitive data inferring a domain specific deficit in TRS populations for verbal, general cognition (IQ) and executive function tasks. Methods: Publications were selected from a systematic search from four databases: PsycINFO, Ovid MEDLINE(R), Scopus and Web of Science. Following inclusion/exclusion criteria, cognitive test outcomes were extracted for each responder group (TRS/NTRS; treatment responders), as well as variables such as age of psychotic illness onset, average chlorpromazine equivalents and duration of illness. Neuropsychological tasks and subtests identified across publications were then grouped into one of seven exclusive cognitive domains (e.g. executive function) prior to analysis based on recommendations from existing literature. Following this, a random-effects model was adopted to test the differences between responder groups in each cognitive domain across publications. Results: From the 17 publications identified, sample sizes ranged from 817 to 36, with the majority of publications using a sample size of ~65 TRS/NTRS cases, and a total sample size of N = 1, 943 across studies. The random-effects model indicates that cases reaching treatment resistance criteria demonstrated marked neuropsychological performance generally across all domains (d = 0.372, 95CIs 0.29; 0.46], p< .001), with this being most marked in tasks of verbal memory and learning (d = 0.49, 95CIs [0.28; 0.70], p<. 001), verbal intelligence and processing (d = 0.38, 95CIs [0.17; 0.58], p< .001), IQ/general cognitive functioning (d = 0.46, 95CIs [0.17; 0.75], p = 0.002), attention, Working memory and Visual-motor/processing speed (d = 0.38, 95CIs [0.24; 0.51], p< 0.001) and executive function (d = 0.41, 95CIs [0.13; 0.68], p = 0.003), with these all demonstrating a close to medium effect size. There was no significant differences between responder groups in test performance for visual-spatial memory and learning (d = .16, 95CIs [-0.16; 0.48], p = 0.334) and visual-spatial intelligence and processing (d = .50, 95CIs [-0.05; 01.04], p = 0.074) tasks. Discussion: In line with existing literature, treatment resistant schizophrenia appears to demonstrate domain specific marked performance on tasks relating to verbal memory, verbal intelligence, as well as tasks relating to executive function, attention and working memory in relation to responders. When considering the clinical importance of identification of treatment resistance in the early disease stages (i.e. at first episode) the use of domain specific cognitive testing could help improve prediction of future antipsychotic response/non-response.